Does personalized melanoma genomic risk information trigger conversations about skin cancer prevention and skin examination with family, friends and health professionals?. (20th July 2017) - Smit, A.K.; Keogh, L.A.; Newson, A.J.; Butow, P.N.; Dunlop, K.; Morton, R.L.; Kirk, J.; Espinoza, D.; Cust, A.E.
Summary: Background: Receiving information about genomic risk of melanoma might trigger conversations about skin cancer prevention and skin examinations. Objectives: To explore conversations prompted by receiving personalized genomic risk of melanoma with family, friends and health professionals. Methods: We used a mixed‐methods approach. Participants without a personal history and unselected for a family history of melanoma ( n = 103, aged 21–69 years, 53% women) completed questionnaires 3 months after receiving a personalized melanoma genomic risk assessment. Semistructured interviews were undertaken with 30 participants in high, average and low genomic risk categories, and data were analysed thematically. Results: From the questionnaires, 74% of participants communicated their genomic risk information with family, and 49% with friends. Communication with a health professional differed by risk level: 41%, 16% and 12% for high, average and low risk, respectively ( P = 0·01). Qualitative analysis showed that perceived 'shared risk' and perceived interest of family and friends were motivations for discussing risk or prevention behaviours. The information prompted conversations with family and health professionals about sun protection and skin checks, and general conversations about melanoma risk with friends. Reasons for not discussing with family included existing personal or family health concerns, or existing high levels of sun protection behaviour among family members. Conclusions: Personalized melanoma genomic risk information can prompt risk‐appropriate discussions about skin cancer prevention and skin examinations with family and health professionals. Sharing this information with others might increase its impact on melanoma prevention and skin examination behaviours, and this process could be used to encourage healthy behaviour change within families. Abstract : What's already known about this topic? The few studies examining disclosure of melanoma‐related genetic test results to family members have been limited to high‐risk individuals with a family or personal history of melanoma, and have followed testing for variants in single genes of high or moderate penetrance. Little is known about reactions of the general population to melanoma genomic risk information (based on common, low‐to‐moderate‐penetrance variants) and whether this information can trigger conversations about melanoma prevention and skin examinations. What does this study add? This mixed‐methods study found that receiving personalized information on genomic risk of melanoma prompted conversations about sun protection (e.g. sunscreen use) and skin examinations, particularly with family and health professionals, and general conversations about melanoma risk with friends. The concept of 'shared risk' was often used when discussing personalized risk information with family members. Communication with health professionals was more frequent among high‐risk participants. What are the clinical implications of this work? Providing personalized melanoma genomic risk information to the general population can prompt risk‐appropriate discussions about skin cancer prevention and skin screening behaviours with family and health professionals. Sharing personalized risk information with others might increase the impact of receiving this information on melanoma prevention and skin examination behaviours, and this process could be used to encourage healthy behaviour change within families. Respond to this article Plain language summary available online